Colossal dielectric constant and a microfarad tunable capacitance in platinum thin film-antimony doped barium strontium titanate Schottky barrier diodes - Sirikulrat N. (2014)
In this research work, the microfarad tunable capacitance in platinum thin film-antimony doped barium strontium titanate (SbBST) Schottky barrier diode with tunabilty characteristics similar to that of the single crystal varactor diode and the related dielectric properties are reported. The apparent colossal dielectric constant (εra) of about 4.4 × 106 arising mainly from the internal barrier layer capacitance (IBLC) at room temperature and a test frequency of 1 kHz is observed. From the Maxwell-Wagner layer model and by using the approximate average grain size and grain boundary thickness of about 10 μm and 0.2 μm, the high εra of 4.4 × 106 can be converted to be the grain boundary dielectric constant of about 88000. Analyses and comparative simulation of the loss tangent of the equivalent circuit to experimental values found that the surface barrier layer capacitance (SBLC) and IBLC are clearly co-related affecting on dielectric properties with the capacitance ratio (CR) of the SBLC to IBLC of about 60:1 at high temperature. The CR projection from high temperature indicates that the depletion layer at the metal-semiconductor interface is very narrow and accumulates highly dense space charges. The total effective depletion width at room temperature, the donor concentration and the mobility of about 44 μm, 7.6 × 1015/cm3 and 0.34 cm2/V-s are respectively obtained. Results from measurements of tunabilty at a higher temperature found that the second transition beyond the ferroelectric-paraelectric transition is observed as the semiconductor-insulator transition or the heat affected tunability cutoff with the transition temperature of about 100 °C. The temperature independent built-in potential with a constant value of 1.5 V prior to the tunability cutoff is obtained. © 2011 Elsevier B.V.